Mechanical qualification of collagen membranes used in dentistry - Emanuela Ortolani; Fabrizio Quadrini; Denise Bellisario; Loredana Santo; Antonella Polimeni; Anna Santarsiero (Istituto Superiore di Sanità, 2015)
AIM. The aim of this work is the qualification of commercially available collagen membranes in a comparative manner. The natural origin of collagen makes standardization difficult. Nevertheless, through dimensional and mechanical measures it is possible to mechanically qualify collagen membranes, and compare them. METHODS. Three commercially available collagen membranes used in Guided Bone Regeneration (GBR) and in Guided Tissue Regeneration (GTR) techniques, namely Bio-Gide, Collprotect and Jason, were chosen for the comparison. Quasi-static (tensile tests) and time-dependent (stress relaxation test) mechanical tests together with a functional test (tear test) were done to determine the responses of collagen membranes under different loading conditions. RESULTS. The tested membranes exhibited different behaviours, different deformability values and thickness, Jason being the thinnest and Bio-Gide the thickest. Similar differences were also observed in terms of surface density. DISCUSSION. Even though clinical observations were not within the aim of this study, our findings indicate that a better understanding of the correlation between mechanical properties and thickness could lead to a more rational design and use of these membranes in the face of specific clinical cases.